The Content Analysis of 7th Grade Teacher Manual Book of “English for Nusantara” in Merdeka Curriculum - Rihandini, Fiona; Aswir, Aswir (BABASAL English Education Journal, 2024)
This study had the purpose to report the analysis results of teacher manual book of “English for Nusantara” for grade VII. The research applied qualitative method with content analysis research design. This study was conducted in even semester of 2022/2023 academic year where the research herself as the instrument of the research. The data were collected from all five chapters in this book together with all three units of each of the chapter. This qualitative research applied conceptual research design. The analysis was carried out by referring to eight aspects junior high school teachers expected to be available in a teacher manual book as found by Fahmi, et.al., (2022) in their research. Those elements covered: layout, teaching procedures, materials explanation, teaching aids, assessment, time allotment, language example and answer key. The analysis results revealed that not all aspects provided in this book, hence, it was less effective to guide teacher in using this manual. However, as the implementation of “Merdeka curriculum’, this manual had already fulfilled what were mandated by the curriculum. This research suggests the authors of the any teacher manual textbook to develop the book based on the teachers’ expectations and needs in order to improve its benefits.